Sistem Informasi Penggajian Dan Perhitungan PPh 21 Pada PT. Lotron Indonesia Bekasi - Reni Muspiawati; Rita Wahyuni Arifin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2015)
Abstract: The era of globalization, information technology moving rapidly. The computer is theequipment created to facilitate human work, to achieve good progress in hardware andsoftware.PT. Lotron Indonesia need an information system that support and facilitate the workprocess. To the writer tries to make research on the system of payroll and income tax reporting21 PT. Lotron Indonesia which is still not computerized. PT. Lotron Indonesia is a companyengaged in the textile field. Existing payroll system at PT. Lotron Indonesia is still done manually,from inputting attendance, payroll calculation, payroll and taxes, preparing reports salaries andtaxes up to data storage - other data related to payroll processing up to journal entries, so asenable during the process occurs recording errors, lack of accurate statements are made and thedelay in the search for the required data. Computerized system is the best solution to solveproblems - problems that exist in this company, as well as the computerized system can achievean activity which is effective and efficient in supporting the activities of this company. Keywords: Computerized system, Existing payroll system, Tax reporting 21 Abstrak: Era globalisasi sekarang ini, teknologi informasi melaju dengan pesat. Adapunkomputer yang merupakan peralatan yang diciptakan untuk mempermudah pekerjaan manusia,sampai mencapai kemajuan baik di dalam hardware dan software.PT. Lotron Indonesiamembutuhkan sebuah sistem informasi yang menunjang dan memberikan kemudahan dalamproses pekerjaannya. Untuk itu penulis mencoba membuat penelitian mengenai sistempenggajian karyawan dan pelaporan PPh 21 pada PT. Lotron Indonesia yang sampai saat inimasih belum terkomputerisasi.PT. Lotron Indonesia ini merupakan perusahaan yang bergerak